PEAT LAND SUITABILITY EVALUATION FOR PEPPER (Piper Nigrum Linn) IN PASAK PIANG VILLAGE SUNGAI AMBAWANG DISTRICTS OF KUBU RAYA REGENCY - Teguh Galang Ukhuwah; Joni Gunawan; Ari Krisnohadi (Jurnal Sains Pertanian Equator, 2018)
ABSTRACT Pasak Piang Village Sungai Ambawang Districts Of Kabupaten Kubu Raya Regency was a location that have a large areas for plantation development, especially for pepper to be the main commodity. This plantation commodity has a strong appeal to individual traders as well as legal entities to make it an object of trade. This study aims to determine the characteristics of peatlands and to determine the level of land suitability for pepper plants (Piper Nigrum Linn) and provide recommendations for improvement. The research method are soil survey using grid system, with 200 x 250 m each survey routes. Soil sample has been analyzed in soil fertility laboratory, University Of Tanjungpura. The result showed that on 80 ha wide area has two land mapping unit, which are typic haplohemist on SPT 1, and typic haplosaprist on SPT 2. The actual land suitability class of SPT 1 and SPT 2 are N1r (temporary not suitable). The inhibited factor of SPT 1 and SPT 2 are root condition (peat depth >200cm). Land management to fix the inhibited factor are soil drainage management, sustainability farming, P and K fertilizer it recommendation will increase the potensial land suitability class to S2 (suitable).